Multiple Logistic Regression on the Outcome of Primiparity With Regressors - Abdulkadir , Abdulkadir; U.F. Abbas; B.A Rashid; Muhammed Bello, Abdulkadir; Idrissa Auwalu, Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The journey of motherhood, particularly the experience of primiparity, holds profound significance in the realm of maternal and childbirth. This study ventures into the intricate dynamics that influence the outcome of primiparity through a comprehensive multiple logistic regression analysis. A cohort of 986 expectant mothers from diverse backgrounds and health profiles became the focal point of this investigation. Six key variables were scrutinized for their impact on the outcome of primiparity: mother’s age, blood pressure, gestation period, labor duration, obesity and time of delivery. The study employed logistic regression to assess the relationship between these variables and the dichotomous outcome of successful or unsuccessful primiparity. The results unveil noteworthy insights, with significant predictors emerging. Blood pressure, labor duration, and obesity were found to be pivotal in shaping the primiparity outcome. Further examination reveals their nuanced relationships, emphasizing the importance of proactive healthcare interventions. This study serves as clarion call to healthcare providers, urging them to prioritize vigilant monitoring of blood pressure, early recognition of labor patterns, and robust support systems to address obesity. These concerned efforts can culminate in safer and healthier childbirth experiences for primiparous women, shaping the well-being of both mothers and their offspring.